2004
DOI: 10.1080/10810730490271665
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Advertising Exposure and Perceptions: Links with Alcohol Expectancies and Intentions to Drink or Drinking in Underaged Youth and Young Adults1

Abstract: This study tests whether the impact of alcohol advertising exposure on intentions to drink and actual consumption is mediated by cognitive responses to advertising messages and positive expectancies about alcohol use. The model was tested using survey data of two important age cohorts, 15 to 20 years (n=608) and 21 to 29 years (n=612). The findings show that alcohol advertising was influential in shaping young people's attitudes and perceptions about alcohol advertising messages. The attitudes and perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 25 publications
(85 reference statements)
3
95
1
3
Order By: Relevance
“…Analyses are based on exposure to advertisements, affective response and infl uence on adolescents' expectations towards alcoholic beverages. 3,12,13,16,26 Certain authors, such as Austin & Mieli, 5 Ellickson et al, 12 Collins et al, 10,11 Grube & Waiters 18 and Fleming et al, 16 explore the responses of those exposed to advertisements as predictors of current and future alcohol use. Other authors, such as Stacy et al 26 and Snyder et al, 25 analyze exposure with a quantitative approach, based on the assumed hours of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses are based on exposure to advertisements, affective response and infl uence on adolescents' expectations towards alcoholic beverages. 3,12,13,16,26 Certain authors, such as Austin & Mieli, 5 Ellickson et al, 12 Collins et al, 10,11 Grube & Waiters 18 and Fleming et al, 16 explore the responses of those exposed to advertisements as predictors of current and future alcohol use. Other authors, such as Stacy et al 26 and Snyder et al, 25 analyze exposure with a quantitative approach, based on the assumed hours of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos têm apontado essa influência da propaganda no consumo (Faria, 2011;Fleming, 2004;Babor, 2003), bem como o fácil acesso dos adolescentes a essa droga (Silva, 2006), corroborando com os resultados desta pesquisa onde a maioria dos adolescentes respondeu que não encontram dificuldades em obter o álcool.…”
Section: Discussionunclassified
“…Researchers have found that advertisements that tell a story, use humor, or include animals are particularly attractive to youth (Chen et al, 2005). Consistent with social cognitive theory (Bandura, 1986(Bandura, , 1994, many studies have found that alcohol advertising changes attitudes toward alcohol, promotes positive expectancies of alcohol use, and increases both intentions to drink and subsequent drinking behavior (Austin et al, 2006;Bekman et al, 2011;Dal Cin et al, 2009;Fleming et al, 2004;Morgenstern et al, 2011;Nicolai et al, 2012;Stacy et al, 1990). …”
Section: Alcohol Advertising and Underage Drinkingmentioning
confidence: 95%